2000
DOI: 10.1103/physrevd.62.044040
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium sequences of irrotational binary polytropic stars: The case of double polytropic stars

Abstract: Solutions to equilibrium sequences of irrotational binary polytropic stars in Newtonian gravity are expanded in a power of = a0/R, where R and a0 are the orbital separation of the binary system and the radius of each star for R = ∞. For each order of , we should solve ordinary differential equations for arbitrary polytropic indices n. We show solutions for polytropic indices n = 0.5, 1, 1.5 and 2 up to 6 orders. Our semi-analytic solutions can be used to check the validity of numerical solutions. PACS number(s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…In particular, we have shown that, in the Newtonian limit, our numerical results coincides with the semi-analytical solutions recently obtained by Taniguchi & Nakamura [63,64] for compressible polytropic stars. The only discrepancies appeared to be due to missing higher order terms in Taniguchi & Nakamura's solutions and not to some inaccuracy of the numerical code.…”
Section: B Tests Passed By the Codesupporting
confidence: 71%
See 3 more Smart Citations
“…In particular, we have shown that, in the Newtonian limit, our numerical results coincides with the semi-analytical solutions recently obtained by Taniguchi & Nakamura [63,64] for compressible polytropic stars. The only discrepancies appeared to be due to missing higher order terms in Taniguchi & Nakamura's solutions and not to some inaccuracy of the numerical code.…”
Section: B Tests Passed By the Codesupporting
confidence: 71%
“…However the analytic solution, based on an expansion up to O((R 0 /d) 6 ), loses its accuracy for very close separations and cannot be used to test the code in this regime. [63,64] along an evolutionary sequence. Solid and dashed lines denote the results of numerical and analytic calculations, respectively.…”
Section: Comparison With Analytic Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, all irrotational binaries of double fluid stars have been computed under the assumption of equal mass [16][17][18][19][20]32,29] except for the Newtonian semi-analytic solutions of the ellipsoidal approximation [33] and the perturbative approach [34,35] 2 , while binary systems of different masses have been calculated in the synchronized cases in Newtonian gravity [36][37][38] and in the first post-Newtonian [39]. In the present paper, we will show numerical results of synchronized and irrotational binary systems composed of different mass stars with the same polytropic equation of state in Newtonian gravity.…”
Section: Introductionmentioning
confidence: 99%